Teaching Strategies and the Holistic Acquisition of Knowledge of the Visual Arts - Eda Birsa (Center for Educational Policy Studies Journal)
Due to the rapid development and advancement within various fields, the scope of knowledge is expanding at a staggering pace. In modern education, experts and teachers makes efforts to eliminate fragmentation of the school curriculum and to modernize the manner of teaching thus optimizing the learning process. In planning art lessons, teachers must adopt an appropriate teaching strategy that enables students to acquire knowledge efficiently and holistically, encouraging the creative solving of art tasks. The present article presents some conclusions of experimental research undertaken to determine the effects of the implementation of a teaching process involving cross-curricular integration. The study involved 274 fifth-grade students and 14 single-class teachers from seven selected Slovenian primary schools. It was found that teachers achieved better learning outcomes by using teaching strategies with cross-curricular integration in sculpting tasks as part of the learning process in art education. The proposed guidelines for teaching art concepts will help teachers to overcome specific obstacles in planning activities for the visual arts learning process, while students will benefit from an increased connection between subjects and integrated knowledge of the visual arts.